Transportability of Conclusions From Confined Field Trials: A Case Study Using the Virus Resistant Transgenic Bean Developed in Brazil - Vesprini, Facundo; Maggi, Andrés Ignacio; López Olaciregui, Magdalena; Módena, Natalia Andrea (Frontiers in Bioengineering and Biotechnology, 2020)
The conceptual framework for Data Transportability, builds on the premise that well-designed studies conducted for the environmental and food/feed risk assessment of transgenic crops may be transportable across geographies. Beyond individual data, provided that certain criteria are met, the general conclusions of comparative assessments of a transgenic crop with its conventional counterpart would also be transportable. In spite of this, many regulatory agencies still require in-country field trials to complete risk assessments of transgenic crops. A sub-team from ILSI Argentina’s (International Life Sciences Institute, Argentina. www.ilsi.org.ar) Biotechnology Working Group tested the applicability of the transportability concept to the case of the golden mosaic virus-resistant transgenic bean, developed by EMBRAPA (EMBRAPA: Brazilian Agricultural Research Corporation). To this end, regulatory confined field trials (CFTs) carried out in Brazil to gather agro-phenotypic and compositional data were analyzed. The transportability of the conclusions of these studies to the bean cropping areas in Argentina was assessed as a conceptual exercise (with no intention to conclude on the biosafety of the common bean event). Comparative studies included the transgenic bean and its conventional parental line and were run in different agroecological environments so that any relevant differences could be observed. The main criteria to enable transportability were set by the sub-team and found to be met by the CFTs carried out in Brazil to inform a potential risk evaluation for Argentina.